Influence of a Survival Swimming Training Programme on Water Safety Knowledge, Attitudes and Skills: A Randomized Controlled Trial among Young Adults in Sri Lanka - Ekanayaka, Jeewanthika; Chan, Kim Geok; Matthews, Bernadette; Dharmaratne, Samath D. (MDPI, 2021)
Drowning among young adults is high in Sri Lanka. Water safety education is a recom-mended strategy for drowning prevention but is often overlooked for young adults. This study aimedto evaluate the effectiveness of an adapted educational intervention, “Swim for Safety” on improvingwater safety knowledge, attitudes and survival swimming skills among undergraduates (19–28 years)in Sri Lanka. This study employed a parallel-group, two-arm randomized controlled trial design.The intervention group (n= 78) received a face-to-face, 12-lesson education programme, and thecontrol group (n= 78) received a brochure and weekly mobile phone messages for six consecutiveweeks. Baseline, post-intervention and three-month follow-up knowledge, attitudes and skills wereevaluated. Knowledge and attitudes were assessed using a self-administered questionnaire and skillswere evaluated following a skills assessment protocol. In total 116 participants, 60 intervention groupand 56 control group, completed the study. At baseline there were no differences between groups inmedian scores of water safety knowledge, attitudes and survival swimming skills. The interventiongroup demonstrated statistically significant increases in median water safety knowledge, attitudesand survival swimming skill scores compared with the control group, following the interventionand maintained at three-month follow-up (p< 0.05). The adapted Swim for Safety programmesignificantly improved water safety knowledge, attitudes, and survival swimming skills amongyoung adults in Sri Lanka. Therefore, it is recommended that the SfS programme be implementedwidely to prevent drowning in young adults.